DIVERSIFIKASI DESTINASI DALAM RANGKA MENDUKUNG KEGIATAN PARIWISATA DAERAH (Studi pada Pelestarian Budaya Damar Kurung di Kabupaten Gresik) - Mazidatus Sakinah; Supriono Supriono (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
Gresik well known with religious tourism place has another attraction that is likely to be developed. Damar Kurung art is one of the typical culture from Gresik. Culture that was originally considered old-fashioned and outdated packed into something new. The diversification of destination products is one of the ways to develop tourism activities in an area and is useful to generate an alternative choice of new tourist destinations for tourists so that researchers lift the title